2006
DOI: 10.1016/j.earlhumdev.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable acceptance by infants: Effects of formula flavors

Abstract: Individual differences in acceptance patterns are evident as early as the child's first experiences with a particular food. To test hypothesis that the flavor of formula fed to infants modifies their acceptance of some foods, we conducted a within- and between-subjects design study in which two groups of 6- to 11-month-old infants were tested on two separate days. One group was currently feeding a milk-based formula whereas the other was feeding a protein hydrolysate formula, a particularly unpleasant tasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Evidence suggests that infants' taste and preferences are formed with the earliest sensory perceptions from amniotic fluid (prenatal) or breast milk (postnatal) of the mother (34)(35)(36) . On the contrary, there is also evidence that formula feed flavours (37,38) and post-weaning feeding practices influence children's conditioning of tastes (36,39) . Thus it may be difficult to disentangle these early-life effects from one another.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that infants' taste and preferences are formed with the earliest sensory perceptions from amniotic fluid (prenatal) or breast milk (postnatal) of the mother (34)(35)(36) . On the contrary, there is also evidence that formula feed flavours (37,38) and post-weaning feeding practices influence children's conditioning of tastes (36,39) . Thus it may be difficult to disentangle these early-life effects from one another.…”
Section: Discussionmentioning
confidence: 99%
“…This underlines the importance of a controlled feeding procedure to assess infant's food acceptance and calls into question data obtained from maternal reports. Because the majority of infants were both breastfed and formula fed, which reflects current feeding practices [28], we were not able to assess the influence of history of milk feeding on fruit and vegetable acceptance, which is however likely to impact solid foods acceptance as suggested by previous studies [10,11,23,29]. Nor were we able to determine in the present study why mothers' ratings of infants' liking of the foods did not change after the exposure period, despite greater acceptance of the food.…”
Section: Discussionmentioning
confidence: 99%
“…For most vegetables, decreased liking (very likely due to boredom) was seen during or after the intervention followed by subsequent increases (a recovery effect). Actually, Mennella, Kennedy, and Beauchamp (2006) suggested that infants might become less responsive to a flavor that they have recently been extensively exposed to, but will develop increased acceptance for that flavor in the longer term. This finding is in line with Cooke (2007) suggesting that maximum effects of exposures may occur after a delay.…”
Section: Likingmentioning
confidence: 99%